Antiseptic pyolytics and warming wet compresses improve the prospect of healing chronic wounds - Aleksandr Urakov; Natalya Urakova; Evgeniy Fisher; Albina Shchemeleva; Anastasia Stolyarenko; Valentina Martiusheva; Marina Zavarzina (Open Exploration Publishing Inc., 2023)
Infection and suppuration of chronic wounds reduce the effectiveness of their treatment with a course of antibiotics and antiseptics combined with frequently renewed dressings. Therefore, daily short-term procedures of cleaning wounds from purulent-necrotic masses by mechanical methods, including the use of cleansing solutions and necrophage fly larvae, are also part of the general practice of chronic wound treatment. But even they do not always provide rapid healing of chronic wounds. In this connection, it is suggested to supplement the treatment of chronic wounds with preparations dissolving dense pus and wound dressings made in the form of warm moist compresses creating a local greenhouse effect in the wounds. Solutions of 3% hydrogen peroxide and 2-10% sodium bicarbonate heated to a temperature of 37°-45°С, possessing alkaline activity at рН 8.4-8.5 and enriched with dissolved carbon dioxide or oxygen gas (due to overpressure of 0.2 atm were suggested as pyolytic drugs. The first results of the use of pyolytics and warm moist dressings-compresses in the treatment of chronic wounds demonstrate a wound-healing effect. It is suggested to consider sanitizing therapy with pyolytics and warm moist wound dressings-compresses as an alternative to the use of modern cleansing solutions and artificial introduction of larvae of the necrophage fly into the purulent masses of chronic wounds to dissolve dense pus and accelerate the healing process.